PENERAPAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 21 PEKANBARU - Fitrika Yanti; Hendri Marhadi; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated by the poor results of social studies third grade students of SD Negeri 21 Pekanbaru with an average of 62.11 with the KKM class IPS is 70. Therefore, researchers conducted a study that aims to improve learning outcomes IPS third grade students of SD Negeri 21 Pekanbaru to implement cooperative learning model Think Pair Share. The research was conducted on April 16 to May 7, 2016. The study design using the PTK (classroom action research) that the implementation is done three cycles, each cycle there are two meetings with the daily test with a different theme each cycle. The subjects were students of class III SD Negeri 21 Pekanbaru totaling 38 people. Data collection instrument in this paper is a sheet activities of teachers, student activity sheets, and learning outcomes. The results showed that the learning outcomes of students increased from prior courses of action with an average of 62.11 increased in the first cycle to 67.50. In the second cycle increased to 76.84 and increased in the third cycle into 82.76. The activities of teachers in the learning process the first cycle of the first meeting of 45.83% and increased in the second meeting be 54.17%. The first meeting of the second cycle activities of teachers increased by 70.83% and in the second meeting be 79.17%. The first meeting of the third cycle activities of teachers increased by 83.33% and in the second meeting be 95.83%. Activity in the learning process the first cycle of the first meeting of 41.67% and increased in the second meeting be 54.17%. The first meeting of the second cycle of student activity amounted to 66.67% and increased in the second meeting to 75%. The first meeting of the third cycle of student activity amounted to 87.5% and increased in the second meeting be 91.67%. Based on the results of action research and data analysis can be concluded that the implementation of cooperative learning model Think Pair Share can improve learning outcomes IPS third grade students of SD Negeri 21 Pekanbaru. From the research, the authors provide recommendations relating to the implementation of cooperative learning model Think Pair Share which teachers should form study groups for students to be actively involved in the learning process, before discussing the group should students have to have opinions of their own thoughts and discussion first with his partner friends, so the atmosphere will be lively group discussion.Keywords : Model Cooperative Learning Think Pair Share, IPS Learning Outcomes